Applying honey dressings to non-healing wounds in elderly persons receiving home care. Issue 3 (August 2019) - Zeleníková, Renáta; Vyhlídalová, Dana
Abstract: Objective: The study aimed to determine the clinical effectiveness of honey dressings in the management of non-healing wounds in elderly persons receiving home care. Material and methods: Design: a prospective interventional study. The sample comprised 40 Czech home care clients (aged over 65 years) with non-healing wounds who were randomly assigned to two groups. Wounds were treated with honey (intervention group) or conventional (controls) dressings. Each wound was studied for three months. A detailed description of a wound (location, size, wound bed, edges, amount of exudate, odor, adjacent skin) were recorded. Wounds were assessed with the Wound Healing Continuum and pain intensity with the Visual Analog Scale. Results: Over the 3-month period, 16 (80%) individuals in the intervention group had their wounds completely healed, as compared with only six (30%) controls. There was no statistically significant difference in wound size between the groups on Day 1 (p = 0.1801). Ninety days later, the difference in wound size between the groups was statistically significant (p = 0.0041). There was a statistically significant difference in pain intensity between the two groups (p = 0.0007), with higher pain scores being indicated by controls. Conclusion: The study results showed that the application of honey dressings to non-healing wounds resulted in faster healing, wound size reduction and lower pain intensity. Highlights: Honey is one of naturally occurring remedies that can be used in the treatment of non-healing wounds. Honey-impregnated dressings significantly reduced the healing time of non-healing wounds in home care setting. Honey-impregnated dressings reduced wound pain intensity in elderly.